High-quality genome sequence and description of Bacillus ndiopicus strain FF3T sp. nov. (November 2015) - Lo, C.I.; Padhmanabhan, R.; Mediannikov, O.; Caputo, A.; Michelle, C.; Faye, N.; Sokhna, C.; Raoult, D.; Fournier, P.-E.; Fenollar, F.
Abstract: Strain FF3 T was isolated from the skin-flora of a 39-year-old healthy Senegalese man. Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry did not allow any identification. This strain exhibited a 16S rRNA sequence similarity of 96.8% with Bacillus massiliensis, the phylogenetically closest species with standing nomenclature. Using a polyphasic study made of phenotypic and genomic analyses, strain FF3 T was Gram-positive, aeroanaerobic and rod shaped and exhibited a genome of 4 068 720 bp with a G+C content of 37.03% that coded 3982 protein-coding and 67 RNA genes (including four rRNA operons). On the basis of these data, we propose the creation of Bacillus ndiopicus sp. nov.